Routines, disruptions, revised decisions: a biographical analysis of vaccination trajectories among Filipino caregivers - Wachinger, Jonas; Reñosa, Mark Donald; Endoma, Vivienne; Landicho-Guevarra, Jhoys; McMahon-Rössle, Shannon A. (Vaccine, 2024)
Background - Individuals’ vaccine attitudes and practices are not static, but instead are shaped and iteratively revised based on new information and experiences. Understanding shifts over the life course could inform novel approaches and indicate opportune points for communicating vaccine information, but little is known about individuals’ vaccination biographies, particularly in low- and middle-income countries. - Methods - To explore vaccination biographies in a setting marked by high proportions of vaccine hesitancy and recent large-scale vaccination discourses, we conducted and biographically analyzed n = 29 narrative in-depth interviews with caregivers of small children in the Philippines. - Results - Our results outline how the perceived relevance of vaccination and an individual’s own attitudes and practices repeatedly changed over the course of their life. While respondents narrated vague memories of early vaccine encounters in their families, at schools, or during vaccination campaigns, vaccine relevance accelerated drastically during respondents’ or their partner’s first perinatal period. Over the following life phase as caregivers, respondents described iterative shifts in their vaccine stance (based on their own experiences, broader discourses, or changing contexts) until their youngest child ‘graduated’ from immunization. Respondents’ later adulthood and old age were commonly marked by little engagement with immunization (except for the COVID-19 vaccines), until the birth of grandchildren sparked renewed motivation to guide younger generations (whether for or against vaccination). - Conclusions - The relevance of vaccination and associated attitudes or practices repeatedly change over the life course. Vaccine promotion efforts could incorporate these biographical dynamics to align with respondents’ informational needs, for example by increased engagement in first perinatal periods, eye-level communication at later phases to acknowledge caregivers’ increased sense of expertise, and encouragement of vaccine confident grandparents to engage in younger generations’ vaccination decisions. Future research should explore transgenerational vaccine trajectories and the potential of biographically targeted promotion efforts.
Online veröffentlicht am 6. Juli 2024
Gesehen am 31.03.2025